(untitled) (Jurnal Peternakan Lingkungan Tropis, 2024)
Carrageenan is additives that contains dietary fiber as a binder, preventing the release of water and stabilizing in restructured processed meat. Carrageenan not only used in the food industry but also in the beverage industry, cosmetic industry and pharmaceutical industry. This study was conducted to determine the effect of adding carrageenan to processed chicken meat products in the form of chicken nuggets at different levels on the physical quality and chemical quality of chicken nuggets. This research was carried out in November 2020 at the Livestock Production and Technology Laboratory, Livestock Nutrition Laboratory and the Samarinda Agricultural Technology Assessment Center (BPTP) Laboratory. This study used a Complete Randomized Design (RAL) with 6 treatments of 4 tests. The treatment carried out was P0 = chicken nuggets without addition of carrageenan, P1 = chicken nuggets with addition of 2% carrageenan, P2 = chicken nuggets with addition of 4% carrageenan, P3 = chicken nuggets with addition of 6% carrageenan, P4 = chicken nuggets with addition of 8% carrageenan, P5 = chicken nuggets with addition of 10% carrageenan. The data were analyzed using ANOVA (Analysis of Variance) if there is a real difference, it will be followed by the BNT (Smallest Real Difference) test with a confidence level of 95%. The results of the study showed that chicken nuggets that were added with carrageenan with different levels showed significantly different results on the pH test, water content test, L* color test before frying, L* after frying, a* after frying and b* before frying while in the water binding test and color test a* before frying and b* after frying showed no significantly different results.